Exegesis of a Renunciation - Esegesi di una rinuncia - Aprile, Francesco (punctum books, 2014)
"The brutality of symbol is visual war. The maze confuses the poetic solitude of the verbal impressed in the pragmatic obol. Manifesto, nervous reflex of language out of control but not without focus, unexpectedly touches the reaction converting the suit interpret-action roar of consciousness. Phonemes-hoplites, the galvanized armor prepares the final siege, it is time to choose which side to fight on. Aprile throws up a challenge: self-centeredness of the word or the reversal of the semantic front against a historic tool devoted to a company withered away and foraging in the cliché, this ultimate foundation of the order-archetype. Prepare for defeat, not to succumb to conceal language accessory and inflamed from of poiesis, and semantic approach exhalation and pray for his death." ~ Cristiano Caggiula "Aprile's writing breathes, survives and is manifested, among dashes, curves, losses, cruises, overlays, erasures, and smudges, smears. A writing dotted with isolated words, they resist to a great catastrophe, arranged in imbalance, moving, equipped with its own breath, your own voice. Aprile's writing is a calligram in which the words are scattered all but disappeared, replaced by stretches of life that run, they run themselves. April drags, hits, dodges, phagocyte and flees, sometimes quickly, sometimes with a certain laziness, out of an area where it shows the drive and exposes the unfinished pulsion of the body. Rhythm writing." ~ Bartolomé Ferrando